2022
DOI: 10.1177/20363613221112432
|View full text |Cite
|
Sign up to set email alerts
|

Supratentorial cortical ependymoma: A systematic literature review and case illustration

Abstract: Cortical ependymomas are currently not considered a subgroup of supratentorial ependymomas; however, there is a growing body of literature investigating the natural history of these lesions compared to supratentorial ependymomas. We performed a systematic literature review of cortical ependymomas with a focus on the natural history, clinical characteristics, and clinical outcomes of these lesions as compared to supratentorial ependymomas. Our search revealed 153 unique cases of cortical ependymomas. The mean a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 63 publications
0
2
0
Order By: Relevance
“…However, our case exhibited a novel YAP1::BEND2 fusion alteration rather than the previously described MN1::BEND2 fusion. To our knowledge, YAP1 fusions have not previously been identified in astroblastoma; rather, YAP1 rearrangements are known to define one subgroup of supratentorial ependymomas 10,20 . Microarray analysis demonstrated chromothripsis of chromosomes X and 11, with results supporting the YAP1 rearrangement.…”
Section: Discussionmentioning
confidence: 73%
See 1 more Smart Citation
“…However, our case exhibited a novel YAP1::BEND2 fusion alteration rather than the previously described MN1::BEND2 fusion. To our knowledge, YAP1 fusions have not previously been identified in astroblastoma; rather, YAP1 rearrangements are known to define one subgroup of supratentorial ependymomas 10,20 . Microarray analysis demonstrated chromothripsis of chromosomes X and 11, with results supporting the YAP1 rearrangement.…”
Section: Discussionmentioning
confidence: 73%
“…To our knowledge, YAP1 fusions have not previously been identified in astroblastoma; rather, YAP1 rearrangements are known to define one subgroup of supratentorial ependymomas. 10,20 Microarray analysis demonstrated chromothripsis of chromosomes X and 11, with results supporting the YAP1 rearrangement. Interestingly, chromothripsis 11 has been reported in several brain tumors, most commonly involving YAP1 in supratentorial ependymomas.…”
Section: Discussionmentioning
confidence: 91%
“…In the pediatric population, the majority of cases are infratentorial and may be complicated by incomplete resection whereas supratentorial lesions are more amenable to complete resection. The role of chemotherapy in children is still under debate but may be beneficial in very young children at risk of extensive radiation damage [ 7 ].…”
Section: Discussionmentioning
confidence: 99%
“…A recently published study by Cuoco et al based on a systematic review of published cases of supratentorial ependymomas showed the mean age of presentation as 21.2 years in a reported number of 153 cases. Out of the total, 47 cases were of pediatric age groups, and only nine cases involved very young children less than three years [ 7 ]. Two other cases of supratentorial cortical ependymoma in very young children were reported by Mehdi et al and Khilji et al in 2016 and 2014, respectively [ 2 , 4 ].…”
Section: Discussionmentioning
confidence: 99%